Hermeneutical Analysis of Simplification and Distortion in @Officialfiqihpernikahan on TikTok: A Study of Hadiths on Prophetic Marriage - Dyna Tauhidah; Ida Rochmawati; Mahfidzatun Nabilah; Khoiriyah Dwi Safitri (Universitas Nurul Jadid, 2025)
This study stems from concerns over the practice of presenting marriage hadith on TikTok, especially the